2017
DOI: 10.19103/as.2016.0011.28
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of environmental enrichment to sustainable poultry production

Abstract: Environmental enrichment comprises stimuli added to the poultry housing environment to enhance the biological adaptation of the birds and improve their welfare. By promoting species-typical behaviour, it has the potential to reduce the risk of harmful behaviours and health conditions, and to guide birds to use the available resources more uniformly. Environmental enrichment may also promote positive emotional states and enhance the birds’ ability to cope with unpredictable environmental changes. In this chapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 119 publications
0
18
0
Order By: Relevance
“…We expected the transect data to be positively associated with increasing environmental complexity based on previous reports suggesting beneficial effects when providing platforms, peat and bales of foraging material alone or in combination [16, 23, 32]. Indeed, we found that the overall welfare problems index declined with increasing environmental complexity, accompanied by reduced mortality and fewer rejections at slaughter due to wounds, underweight birds and overall.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We expected the transect data to be positively associated with increasing environmental complexity based on previous reports suggesting beneficial effects when providing platforms, peat and bales of foraging material alone or in combination [16, 23, 32]. Indeed, we found that the overall welfare problems index declined with increasing environmental complexity, accompanied by reduced mortality and fewer rejections at slaughter due to wounds, underweight birds and overall.…”
Section: Discussionmentioning
confidence: 80%
“…Environmental enrichment refers to additions and modifications to the housing environment that increase environmental complexity, stimulate species-specific behaviour and facilitate biological functioning, thereby improving animal welfare [14, 15]. Elevated resting surfaces such as perches, platforms and boxes can serve as environmental enrichment for broilers [16]. Use of such structures may strengthen muscles and joints and enhance the blood supply to the legs, wings and heart [17].…”
Section: Introductionmentioning
confidence: 99%
“…Plus, we will review how environmental enrichment and modifications can stimulate active behavior in broilers and discuss which factors to consider when devising enrichment strategies to improve broiler chicken activity and behavior. 3) Environmental enrichment and its relationship with indicators of welfare, building on the reviews of Riber et al (2018) , Pedersen and Forkman (2019) , and Estevez and Newberry (2017) and providing an update on scientific literature regarding effects of environmental enrichment on various welfare indicators for broiler chickens. Finally, 4) a case study focusing on the application of enrichments in commercial broiler chicken production, presenting how a large-scale company has engaged producers to practically implement effective environmental enrichment strategies on-farm.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental enrichment has been defined as a modification of the environment in which the animals are kept, allowing the animals to perform more of their species-specific behavioural repertoire and thus accommodating a larger range of behavioural choices (Estevez and Newberry, 2017). Environmental enrichments may relate to specific behavioural requirements of chickens, for example, they may meet the need for elevated resting, or for exploration pecking, and sometimes combine these different functions.…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…The majority of broiler chickens, especially fast-growing breeds in conventional systems, are housed in relatively barren environments, and despite the increased number of scientific studies reporting potentially positive effects of environmental enrichment on broiler welfare, environmental enrichment is only applied on a limited scale in practice. One reason might be that farmers and integrations often think that environmental enrichment increases production costs and thus reduces economic competitiveness (Estevez and Newberry, 2017). However, this does not take into account potential benefits of environmental enrichment on broiler health.…”
Section: Environmental Enrichmentmentioning
confidence: 99%